In vivo assessments to detect antimalarial resistance - Dhorda, M; Dondorp, A (Humana Press, 2019)
In vivo drug clinical trials are the gold standard for assessing the therapeutic efficacy of antimalarials. They must be conducted in a rigorous and standardized manner so that the resistance of antimalarial drugs can be compared both in time and in space. This chapter presents the methodology for conducting such clinical studies of antimalarials for the treatment of uncomplicated malaria and describes the logistical difficulties and limitations of this methodology. Finally it highlights the importance of such knowledge in preventing resistance, in prolonging the utility of existing antimalarial drugs, and in ensuring that all individuals and populations suffering from malaria get the right malaria treatment at the right time.